UPAYA ORANGTUA DALAM MENANAMKAN PENDIDIKAN AGAMA ISLAM PADA ANAK USIA DINI - Baharuddin, Ismail (IAIN Padangsidimpuan, 2016)
Parents are first and foremost educators to the educational success of a child, because since the birth of a child into the world, his parents are the first people to interact with a child. The success of a child is in the hands of both his parents. And a child needs of guidance, attention, and affection from their parents, let alone a young child.Â Â Both parents are not just parents who can bear children, but should be good to educate children properly. Both parents help the child becomes a responsible adult, virtuous, and gives the best to the community and to fear God. Parents should always instill religious education for their children starting at an early age, because of the education since taught his children to always accustomes to in everyday life. Many parents assume that their responsibility is only a fulfillment course, if it has been filled with biological needs, such as food and clothing, the obligations as a parents have fnished. Parents are first and foremost educators that are required by a child.